2019
DOI: 10.1002/cam4.2533
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine‐related adverse events associated with immune‐checkpoint inhibitors in patients with melanoma

Abstract: BackgroundImmune‐checkpoint inhibitors have been shown to improve survival in melanoma patients, but can also trigger immune‐related endocrinopathies, especially hypophysitis and thyroid dysfunction.MethodsTo assess the incidence and the spectrum of endocrinopathies in melanoma patients treated with immunotherapy a prospective observational study was conducted. Forty out of 339 patients, treated with immune‐checkpoint inhibitors, developed endocrinopathies. All patients had hormonal functional tests at screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
0
27
2
1
Order By: Relevance
“…The diagnosis of ICI-induced hypophysitis is based on recent use of these drugs in patients with malignancies. The commonest symptoms include fatigue and headaches in 59–73% and 21–80% of cases, respectively, whereas visual disturbances and DI are relatively rare [9, 43, 63-65]. Most cases are diagnosed during regular follow-up of pituitary function performed before every cycle of therapy for at least the first 3 months [1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of ICI-induced hypophysitis is based on recent use of these drugs in patients with malignancies. The commonest symptoms include fatigue and headaches in 59–73% and 21–80% of cases, respectively, whereas visual disturbances and DI are relatively rare [9, 43, 63-65]. Most cases are diagnosed during regular follow-up of pituitary function performed before every cycle of therapy for at least the first 3 months [1].…”
Section: Resultsmentioning
confidence: 99%
“…Most cases are diagnosed during regular follow-up of pituitary function performed before every cycle of therapy for at least the first 3 months [1]. Patients with ICI-induced hypophysitis usually present with TSH (84%), adrenocorticotropic hormone (80%), and gonadotropin (76%) deficiency [39, 65].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by our group reported for the first time that sequential treatment with anti-CTLA-4 and anti-PD1 agents increased the risk of developing hypophysitis to a level as high as that of combination therapy. 26 Furthermore, high rates of hypophysitis (grade 3 or 4 toxicity) have been reported in patients receiving adjuvant treatment with prostate cancer cell vaccine or bevacizumab. 27,28 In contrast, no increased incidence of hypophysitis was observed with the combination of ipilimumab with chemotherapeutic agents such as carboplatin, dacarbazine, paclitaxel and fotemustine or targeted agents including vemurafenib and dabrafenib compared to monotherapy with ipilimumab.…”
Section: Prevalence and Epidemiology Of Ipilimumab-induced Hypophysitismentioning
confidence: 99%
“…10 In fact, recent case series report that adrenocorticotropic deficiency is the most common hormonal insufficiency observed in patients with ICI-related hypophysitis. 26,47 It is characterized by a low-or low-normal early morning cortisol level in the setting of an inappropriately low or normal adrenocorticotropin hormone (ACTH). Hypogonadotropic hypogonadism is also common while the prevalence of growth hormone (GH) deficiency is unclear due to lack of confirmation of GH deficiency in most studies.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Moreover, endocrinopathies are more common when two ICIs are used together [ 2 ]. The thyroid and pituitary glands are the most commonly affected endocrine organs [ 3 ], however cases of type 1 diabetes mellitus (including diabetic ketoacidosis) [ 4 ], primary adrenal insufficiency [ 5 ], Cushing’s Syndrome [ 6 ], diabetes insipidus [ 7 ] and hypoparathyroidism [ 8 ] have all been reported. Patients can develop problems with one or multiple endocrine organs.…”
Section: Introductionmentioning
confidence: 99%